2007
DOI: 10.1038/ja.2007.50
|View full text |Cite
|
Sign up to set email alerts
|

Cell-adhesion Inhibitors Produced by a Sea Hare-derived Periconia sp.

Abstract: Peribysin J and macrosphelide M have been isolated from a strain of Periconia byssoides originally isolated from the sea hare Aplysia kurodai. Their absolute stereostructures have been elucidated on the basis of spectroscopic analyses using 1D and 2D NMR techniques and some chemical transformations including the modified Mosher's method. These fungal metabolites inhibited the adhesion of human-leukemia HL-60 cells to humanumbilical-vein endothelial cells (HUVEC).Keywords fungus, cell-adhesion inhibitor, periby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…Peribysins A–J ( 18 – 27 ) are a group of eremophilane-type sesquiterpenoids produced by Periconia byssoides which was isolated from the sea hare Aplysia kurodai [1821]. They have raised considerable interest and have become the subject of synthetic efforts due to their ability of inhibit the adhesion of human-leukemia HL-60 cells to HUVEC at lower μM concentration, and thus are two orders of magnitude more potent than the standard control in this assay system, herbimycin A.…”
Section: Examples Of Terpenoidsmentioning
confidence: 99%
“…Peribysins A–J ( 18 – 27 ) are a group of eremophilane-type sesquiterpenoids produced by Periconia byssoides which was isolated from the sea hare Aplysia kurodai [1821]. They have raised considerable interest and have become the subject of synthetic efforts due to their ability of inhibit the adhesion of human-leukemia HL-60 cells to HUVEC at lower μM concentration, and thus are two orders of magnitude more potent than the standard control in this assay system, herbimycin A.…”
Section: Examples Of Terpenoidsmentioning
confidence: 99%
“…If macrosphelide D has the same configurations at the pairs of adjacent stereocenters as macrosphelides A and E, then it could be either 10 (C3 S) or 11 (C3 R). Structure 11 is already a known natural product called macrosphelide M. 33 Unfortunately, the spectra of macrosphelide D are reported in chloroform- d 1 and those of macrosphelide M are in acetone- d 6 , so we could not assess at this point whether the two natural samples are the same or different. However, since macrosphelides A and D were isolated from the same broth, the structure 10 seems more likely than 11 .…”
Section: Resultsmentioning
confidence: 99%
“…They are also known and widely studied because some species belonging in it are responsible for severe diseases of cereal crops such as milo disease [2]. Previous chemical investigations have shown that the genus Periconia is a rich source of terpenes, including monoterpene [3], sesquiterpenes [4][5][6][7], and diterpenes [8]. In our ongoing search for bioactive secondary metabolites from endolichenic fungi, a chemical investigation focused on a strain of this genus (19-4-2-1) was carried out, which led to the isolation of a new cadinane-type sesquiterpene, namely pericoterpenoid A (1).…”
Section: Introductionmentioning
confidence: 99%